ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU INVESTASI MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS NEGERI SURABAYA - Arlin Hana Madu; Moh. Danang Bahtiar (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
In the era of globalization, rapid economic development is increasingly makingindividuals in the management of their financial resources have to experienceimprovement. This study aims to determine and analyze the factors that influenceinvestment behavior, including financial literacy, income level, and lifestyle,simultaneously and partially affecting the investment behavior of UNESA Facultyof Economics and Business students. Based on the results of the t test, thesignificance value of the results of the analysis of the financial literacy variable was0.047, the income level was 0.134, and the lifestyle was 0.012. Partially, financialliteracy and lifestyle have an effect on investment behavior with a significance valueof <0.05, and the level of income has no effect partially because the significancevalue is >0.05. While the F test obtained a significance value of 0.001, This showsthat financial literacy, income level, and lifestyle partially influence the investmentbehavior of FEB Unesa students. Besides the t test and F test, the adjusted R valueis 0.385, meaning that 38.5% of investment behavior is influenced by financialliteracy, income level, and lifestyle. While 61.5% is influenced by other variablesnot explained in this study,